Omveien hjem. "Hans og Grete" i klasserommet - Gaasland, Rolf (Nordlit, 2022)
The article argues for the value of working hermeneutically in a methodical way with literary texts in the classroom. It is based on the belief that being responsive to another human being’s world of thought is valuable in itself and also that the interpretive effort is inextricably linked with virtues such as self-work and self-knowledge. The article is divided into three main parts. Firstly, it offers an example of what an interpretation of the folk-tale «Hansel and Gretel» might look like when it aims to realize Hans-Georg Gadamer's notion of methodological awareness. Gadamer's notion of methodological awareness is then further elaborated on before the article finally presents and recommends a hermeneutical methodology designed to help pupils/students practice a methodical awareness when working with literary texts